Can we replace adjuvant chemotherapy with surveillance for stage IA-C immature ovarian teratomas of any grade? an international multicenter analysis. (September 2020) - Bergamini, Alice; Sarwar, Naveed; Ferrandina, Gabriella; Scarfone, Giovanna; Short, Dee; Aguiar, Xianne; Camnasio, Cristina; Kaur, Baljeet; Savage, Philip M.; Cormio, Gennaro; Lim, Adrian; Pignata, Sandro; et al.
Abstract: Background: The role of surveillance after surgery for stage IA-C grade 2 (G2) or grade 3 (G3) immature teratomas (ITs) is controversial with many guidelines advocating adjuvant chemotherapy. Here, we investigate the safety of surveillance in stage IA-C G1-3 ITs. Methods: Clinicopathological data were analysed on postpubertal patients with stage I pure ITs in Multicenter Italian Trials in Ovarian Cancer centres and at Charing Cross Hospital, UK, between January 1985 and January 2018. Results: Of 108 stage I patients, 66 (61.1%), 3 (2.8%) and 39 (36.1%) were International Federation of Gynecology and Obstetrics IA, IB, IC, respectively, with 31 (28.7%), 41 (38%) and 36 (33.3%) having grade 1 (G1), 2 and 3 disease, respectively. After surgery, 27 patients (25%) had adjuvant chemotherapy and 81 (75%) surveillance. There was no significant increase in the risk of malignant (G2-3 IT) relapse (9/81 vs 2/27; p = 0.72) or in disease-free survival (DFS) or overall survival in the surveillance vs chemotherapy groups. The median time to relapse was 17.8 months (range: 3–47) with no significant difference between surveillance or chemotherapy groups. The median follow-up was 64.3 months (Interquartile range (IQR) 22.2–101.7). Chemotherapy induced cures in all except for one patient who did not follow the surveillance protocol due to pregnancy and died of disease. Univariate and multivariate analyses revealed that only tumour grade (hazard ratio [HR] = 3.11; p = 0.02) and complete surgical staging (HR = 0.2; p = 0.01) were independent prognostic factors for decreased DFS. Conclusion: The present study suggests that in the adult setting careful surveillance appears to be an acceptable alternative to adjuvant chemotherapy for stage IA-C ITs of any grade, properly staged and with negative postoperative tumour markers. Highlights: Surveillance does not worsen prognosis of postpubertal stage I ovarian immature teratomas. When suspecting a recurrence, surgery is recommended to assess the presence of immature disease. Adjuvant chemotherapy should be reserved for the treatment of recurrent immature grade 2-3 disease.